Development of a novel ice cream with hemp milk based on chia seed mucilage as a stabiliser : a thesis presented in partial fulfilment of the requirements for the degree of Master of Food Technology, Massey University, Manawatu, New Zealand - Zhang, Weilun (Massey University, 2024)
The majority of commercial ice cream products are made from dairy, which can lead to health issues for consumers with lactose intolerance and casein allergies. Commercial stabilisers are used in ice cream formulas to provide maximum performance in meeting several requirements, including consumer demands, transport, and cost-effectiveness. As a result, there is a significant need for consumers to discover substitute products that offer comparable health benefits to dairy products and products with clean labels. If there is an ice cream that uses natural sources of stabilisers that can make the ice cream label look simpler and cleaner while having health benefits, it will probably be competitive in the marketplace. Hemp seeds are rich in essential elements needed by the human body. Consequently, food manufacturers have taken an interest in hemp milk because of its exceptional nutritional content. Currently, the food industry has not made any progress in creating ice creams that contain hemp milk to improve their nutritional content. Hemp milk, on the other hand, has a specific flavour, and the direct use of hemp milk in ice cream production may have a negative impact on the product's flavour and aroma. The differences in the type and content of proteins and fats between hemp milk and cow milk may also have an unknown effect on the physical and chemical properties of the ice cream (e.g., texture, overrun, and ice crystal content). This study substituted five levels of hemp milk (0%, 25%, 50%, 75%, and 100%) for cow milk using chia seed mucilage (CSM) as stabiliser. The aim was to determine the impact of the added hemp milk on the ice cream's properties and its storage stability after 21 days to determine the most suitable hemp milk content. This study was conducted in four phases. In the first phase, chia seeds were soaked, stirred, and centrifuged to separate CSM. The extracted CSM was dried and stored after measuring its water activity and moisture content. Then, hemp milk was extracted from hemp seeds using a high-shear blender, homogenised, and filtered. Its total solid content, dissolved sugar content, dietary fibre content, and nutritional properties were measured and stored under refrigeration. In the second phase, five ice cream samples containing different amounts of hemp milk were prepared. The formulation containing 25% hemp milk was selected as the best-performing formulation based on the summary of the opinions of the focus groups (n = 6), pH, overrun, colour, and melting properties. In the third phase, the physicochemical and nutritional characteristics of the ice cream were analysed and discussed. In addition to this, a consumer sensory panel (n = 35) assessed the overall acceptability and Just-About-Right (JAR) of the best formulation ice cream sample. The average acceptability score of the ice cream containing 25% hemp milk was 6.75, and the JAR results showed that the JAR percentage was above 70% for all the attributes except for taste and aroma. The indicators of taste were found to fall within the noteworthy range by penalty analysis, but not in the high impact (>0.5) range. The results revealed that the ice cream formulation containing 25% hemp milk has ideal sensory and physicochemical properties. In the fourth phase, the stability of the best formulation ice cream during storage (-19 °C) for a period of 21 days was evaluated by measuring the pH, colour, and hardness and by consumer sensory evaluation of the best formulation ice cream. Although the L* a* values in colour and hardness of the ice cream showed statistically significant changes (p<0.05) during storage, the b* values in the colour and pH of the ice cream remained stable (p > 0.05). Meanwhile, the consumer sensory evaluation results showed that the product was still considered acceptable after 21 days of storage.
Figures 2.1 & 2.2 (=Galanakis, 2022b Figs 1.2 & 1.3), 2.5 (=Vahanvaty, 2009 Fig 4) and 2.6 (=Salgado-Cruz et al., 2013 Fig 6) were removed for copyright reasons.
Keywords: 300602 Food chemistry and food sensory science